Long-term efficacy of macrolide treatment in idiopathic pulmonary fibrosis: a retrospective analysis - Kuse, Naoyuki; Abe, Shinji; Hayashi, Hiroki; Kamio, Koichiro; Saito, Yoshinobu; Usuki, Jiro; Azuma, Arata; Kudoh, Shoji; Gemma, Akihiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background and objective: There is growing evidence for anti-inflammatory activities of macrolides in chronic respiratory diseases, such as diffuse panbronchiolitis, cystic fibrosis, or chronic bronchitis. The long-term effect of macrolides in idiopathic pulmonary fibrosis (IPF) is unknown. This study was aimed to investigate the effect of macrolide therapy on the frequency of acute exacerbation (AE) and the mortality in IPF. Methods: A total 52 IPF patients who were treated by combination of conventional agents with or without macrolides were retrospectively reviewed. The primary endpoint was the incidence of AE in IPF patients. We also observed survival rate after the treatment with or without macrolides. Results: AE was observed in 4 of 29 cases (13.8%) treated with macrolides and 8 of 23 cases (34.8%) treated without macrolides, respectively during 36 months. AE free survival rate of macrolide group was significantly better than that of non-macrolide group (logrank p=0.027). Survival rate of IPF patients with macrolide therapy was significantly better than that of patients without macrolide therapy (p=0.047). Conclusion: Our results indicate the potential beneficial efficacy of macrolide therapy combined with oral corticosteroids, immunosuppressive or anti-fibrotic agents in IPF.